2019
DOI: 10.1177/1534735419880598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Exercise Interventions on Quality of Life in Breast Cancer Patients: A Randomized Controlled Trial

Abstract: Purpose: The aim of the present study was to evaluate the effects of different exercise interventions on quality of life parameters in breast cancer patients during 1 year of outpatient rehabilitation. Material and Methods: A total of 115 breast cancer patients met the eligibility criteria and completed the study. Participants were randomly allocated for the water exercise interventions (group A, n = 45), for the Pilates exercise interventions (group B, n = 40), and yoga exercise interventions (group C, n = 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 27 publications
3
70
0
5
Order By: Relevance
“…The risk of bias assessed by NIH quality assessment tool is summarized in Table 2 . Five studies had moderate quality,[ 20 25 26 27 28 ] one study found to have good quality[ 29 ] and one study was in low quality. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of bias assessed by NIH quality assessment tool is summarized in Table 2 . Five studies had moderate quality,[ 20 25 26 27 28 ] one study found to have good quality[ 29 ] and one study was in low quality. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…Out of seven studies, three studies were conducted in USA, two studies in Australia, one study in Poland, and one in Ukraine all of which were from developed countries and none from developing regions. Three studies were randomized controlled trials,[ 28 29 30 ] three were single group pre–posttest,[ 20 26 27 ] one study was controlled clinical trial,[ 25 ] and four studies were conducted at pilot level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise on the affected side of the limbs was aimed for the affected side of the breast, early use of low-intensity, low-amplitude, small joint movement can relieve joint stiffness, promote blood flow of the affected limb, improve breast swelling without increasing the pain of the limbs ( 24 , 25 ). Yoga exercises can significantly reduce the pain and swelling of breasts in patients with breast cancer ( 26 , 27 ). Rehabilitation yoga exercise was introduced after the patient had no discomfort, and simple upper limb stretching Yoga exercises were selected.…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al 23 demonstrated good adherence to, safety and effectiveness of resistance training with Pilates chair equipment for breast cancer survivors. Odynets et al 24 compared Pilates training with other physical activity modalities and found that water exercise intervention is more effective for improving emotional well-being and decreasing negative symptoms associated with breast cancer treatment compared with Pilates. However, various intervention methods, duration, and intensity of exercises create some difficulties in comparing the results obtained in the context of the current research.…”
Section: -10mentioning
confidence: 99%